Anti-inflammatory effects of CBD in human microglial cell line infected with HIV-1 - Adriana Yndart Arias; Nagesh Kolishetti; Arti Vashist; Lakshmana Madepalli; Lorgeleys Llaguno; Madhavan Nair (Scientific Reports, 2023)
Abstract Human immunodeficiency virus (HIV) infection is associated with a chronic inflammatory stage and continuous activation of inflammasome pathway. We studied the anti-inflammatory effects of the compound cannabidiol (CBD) in comparison with Δ (9)-tetrahydrocannabinol [Δ(9)-THC] in human microglial cells (HC69.5) infected with HIV. Our results showed that CBD reduced the production of various inflammatory cytokines and chemokines such as MIF, SERPIN E1, IL-6, IL-8, GM-CSF, MCP-1, CXCL1, CXCL10, and IL-1 β compared to Δ(9)-THC treatment. In addition, CBD led to the deactivation of caspase 1, reduced NLRP3 gene expression which play a crucial role in the inflammasome cascade. Furthermore, CBD significantly reduced the expression of HIV. Our study demonstrated that CBD has anti-inflammatory properties and exhibits significant therapeutic potential against HIV-1 infections and neuroinflammation.